Analysis of Financing Prospects of Mandiri Syariah Bank (BSM) in Pemalang - Ruchul Qisthi Izzati; Nining Nurhasanah (Gorontalo State University, 2021)
The author conducted research on the Prospect Analysis of Bank Syariah Mandiri (BSM) in Pemalang City, the majority of which are inhabited by Muslims. So that the urgency of establishing a Sharia Financial Institution is very important. Because if it is allowed, the community will be entangled in transactions that are prohibited in Islam, namely usury. The aim is to analyze the prospects for Bank Syariah Mandiri (BSM) in Pemalang City and to find out how much potential the establishment of Bank Mandiri Syariah in Pemalang City. The research method used is a descriptive exploratory research model with a quantitative approach and analysis with a qualitative approach. The conclusion of this study is that based on the macroeconomic aspect, the establishment of Bank Syariah Mandiri in Pemalang City has a very big opportunity to be established. In the aspect of operational analysis, there is an appropriate place for the establishment of Bank Syariah Mandiri in Pemalang City. The right place to set up Bank Syariah Mandiri is located at Jalan Jend. Sudirman Mulyoharjo, Pemalang Regency. And in the market aspect, the authors conducted a survey on SMEs in Pemalang City. And the result is 79% of SMEs in Pemalang City are interested in the existence of Bank Syariah Mandiri. Keywords: Financing; Prospect; Prospect Analysis